Carbon nanotube-supported high entropy boride cathode material and preparation method and application thereof
By using high-entropy boric positive electrode material loaded by carbon nanotubes in sodium ion batteries, the problem of insufficient capacity and cycle stability of the positive electrode material of sodium ion batteries is solved, high specific capacity and excellent cycle stability are achieved, and the preparation process is simplified , easy to promote and apply.
Patent Information
- Application Number
- CN202411313104.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The low capacity and poor cycle stability of sodium ion battery cathode materials limit their practical application. The existing technology is complex and the variety of raw materials is not conducive to promotion.
Using high-entropy boricide positive electrode material loaded by carbon nanotubes, a three-dimensional mesh support structure of amorphous high-entropy boricide (MnFeCoNiZnAl-B) and carbon nanotubes was prepared by chemical liquid phase method to form high specific capacity and good cycle stability material of sexuality.
High specific capacity and excellent cycle stability in aqueous sodium ion batteries are achieved, providing a specific capacity of 174 mAh g-1, with a capacity retention rate of more than 90% after 1000 cycles, and a wide voltage window and high conductivity.
Smart Images

Figure CN118867206B_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to the field of sodium ion batteries, in particular to a high-entropy boride positive electrode material supported by carbon nanotubes and a preparation method and application thereof. Background Art
[0002] As the global energy crisis and environmental pollution problems intensify, it is particularly important to develop efficient and stable new energy technologies. As a promising energy storage technology, sodium-ion batteries have attracted widespread attention. However, the problems of sodium-ion battery cathode materials, such as low capacity and poor cycle stability, limit their practical application.
[0003] At present, there are already positive electrode materials that improve battery capacity and cycle stability in the prior art. For example, in the patent with application publication number CN116093326A, a sodium ion battery positive electrode material and its preparation method and application are disclosed, wherein the sodium ion battery positive electrode material includes a high entropy layered transition metal oxide and a solid electrolyte coating layer coated on the surface of the high entropy layered transition metal oxide; wherein the chemical formula of the high entropy layered transition metal oxide is NaTMO2, and TM includes at least five of Li, B, Mg, Al, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Sn, Sb, Te, Ir and Bi. The sodium ion battery positive electrode material of the invention shows good structural stability, with a specific capacity of 128.1 mAh / g and a cycle stability of 500 weeks of up to 93.0%. Such materials show good application prospects in the field of large-scale energy storage, but there is still room for improvement. In addition, the raw materials of the sodium ion battery positive electrode material of this invention are of various types and the preparation method is relatively complicated, which is not conducive to promotion and application. Summary of the invention
[0004] The technical solution of the present invention aims at the technical problem that the existing technical solutions are too single, and provides a solution that is significantly different from the existing technology. It mainly provides a high-entropy boride positive electrode material loaded with carbon nanotubes and a preparation method and application thereof, so as to solve the technical problem that the capacity and cycle stability of the positive electrode material of the sodium ion battery raised in the above background technology need to be improved.
[0005] The technical solution adopted by the present invention to solve the above technical problems is:
[0006] A carbon nanotube-loaded high-entropy boride cathode material comprises carbon nanotubes (CNTs) in a three-dimensional network support structure and high-entropy boride (MnFeCoNiZnAl-B) attached to the carbon nanotubes, wherein the high-entropy boride has an amorphous structure and contains a variety of multivalent metals; the raw materials of the carbon nanotube-loaded high-entropy boride cathode material comprise metal salts, boric acid and carbon nanotubes, the total molar ratio of the boric acid to the metal salt is 1:(1.9-2.1), and the total mass ratio of the carbon nanotubes to the metal salt is 1:10.
[0007] Preferably, the metal elements of the high entropy boride include Mn, Fe, Co, Ni, Zn and Al.
[0008] Preferably, the metal salts include Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O.
[0009] Preferably, the molar ratio of Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O is (0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1).
[0010] Specifically, the chemical formula of the high entropy boride positive electrode material is (MnFeCoNiZnAl) 1 / 6 B / CNT.
[0011] The present invention also provides a method for preparing the above-mentioned carbon nanotube-loaded high entropy boride positive electrode material, wherein the high entropy boride (MnFeCoNiZnAl-B) is combined with the carbon nanotubes by a chemical liquid phase method; specifically comprising the following steps:
[0012] S1. Raw material preparation: taking metal salt, boric acid and carbon nanotubes according to the mass ratio, pre-cleaning the carbon nanotubes and dispersing them in deionized water to prepare a CNT dispersion for later use;
[0013] S2, dissolving the metal salt and boric acid prepared in step S1 in deionized water under ice bath conditions, stirring evenly to obtain a mixed solution;
[0014] S3, adding the CNT dispersion to the mixed solution of step S2, and continuing to stir until the mixture is uniform;
[0015] S4, transferring the mixed solution to which CNTs are added in step S3 to a high-pressure reactor, and performing a hydrothermal reaction to form a desired amorphous high-entropy boride;
[0016] S5. After the reaction is completed, the mixture is naturally cooled to room temperature, and the product is centrifuged and washed several times with deionized water and ethanol to remove possible impurities and unreacted substances;
[0017] S6. Dry the product to obtain a black powder which is a high entropy boride / carbon nanotube composite material.
[0018] Specifically, in step S3, the stirring time is 30-40 minutes.
[0019] Specifically, in step S4, the temperature of the hydrothermal reaction is 180° C., and the reaction time is 24 hours.
[0020] Specifically, in step S6, the drying temperature is 80° C. and the drying time is 11-12 hours.
[0021] The present invention also provides an aqueous sodium ion battery, wherein the positive electrode adopts the high entropy boride positive electrode material loaded by the carbon nanotubes, the negative electrode adopts metallic sodium or sodium alloy, and the electrolyte adopts an aqueous electrolyte solution.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The carbon nanotube-supported high entropy boride positive electrode material provided by the present invention comprises carbon nanotubes in a three-dimensional network support structure and high entropy boride attached to the carbon nanotubes, wherein the high entropy boride has an amorphous structure and contains a variety of multivalent metals. It exhibits excellent electrochemical performance in aqueous sodium ion batteries, including high specific capacity and good cycle stability. The main reasons are:
[0024] ① High configuration entropy: High entropy materials have higher configuration entropy, which helps prevent instability of electrodes under long-term operation and high current density;
[0025] ② Advantages of amorphous structure: Amorphous high-entropy borides have higher surface active sites than general high-entropy compounds, and can provide more oxidizable and reductive active sites, which is beneficial for energy storage;
[0026] ③ Rich active sites: The material contains a variety of multivalent metals, which creates abundant oxidizable and reductive active sites for energy storage and helps improve electrochemical performance;
[0027] ④ Electronic structure optimization: The introduction of inactive metals (such as Zn and Al) changes the local electronic structure and increases the number of free electrons around high-valence metals, thereby improving the conductivity and ion diffusion capacity of the material.
[0028] ⑤The role of the three-dimensional network support structure: The three-dimensional network structure of carbon nanotubes can effectively avoid the aggregation of amorphous boride particles, ensure the high specific surface area and good electrical conductivity of the material, and help improve the specific capacity and cycle stability.
[0029] (2) The high entropy boride of the present invention is combined with carbon nanotubes through a chemical liquid phase method. Due to the small grain size of amorphous boride particles, they are directly dispersed and attached to the carbon nanotubes during the growth process to combine with them. Different from ordinary physical combination, the combination during the growth process will cause its contact resistance to be greatly reduced, which can further improve the overall conductivity of the electrode.
[0030] (3) Experiments show that the aqueous sodium ion battery using high entropy boride supported by carbon nanotubes as the positive electrode material in the present invention has a high -1 At a current density of 174 mAh g -1 After 1000 cycles, the capacity retention rate exceeds 90%, showing excellent cycle stability. In addition, it also has the characteristics of wide voltage window and high conductivity.
[0031] (4) The raw materials of the positive electrode material provided by the present invention only include metal salt, boric acid and carbon nanotubes. When preparing, first prepare the raw materials according to the ratio, then mix the materials (first dissolve the metal salt and boric acid in water and mix them evenly, then add carbon nanotubes and mix them evenly), then transfer them to a high-pressure reactor for hydrothermal reaction, cool them, remove impurities and dry them to obtain the positive electrode material. The preparation method of the positive electrode material provided by the present invention is simple and easy to implement, and is convenient for promotion and application.
[0032] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 In the present invention, (MnFeCoNiZnAl) 1 / 6 B. Schematic diagram of the optimized structural model, where (a) is a top view, (b) is a side view, and (c) is a schematic diagram of the sodium ion adsorption process;
[0034] Figure 2 It is the structural model diagram of the product in the comparative example, where (a) is (MnFeCoNi) 1 / 4 (b) is the structural model diagram of MnB, (c) is the structural model diagram of FeB, (d) is the structural model diagram of CoB, and (e) is the structural model diagram of NiB;
[0035] Figure 3 For different Na + At adsorption concentration, (MnFeCoNiZnAl)1 / 6 The formation energy of B is E f and simulated discharge voltage curve;
[0036] Figure 4 The maximum theoretical specific capacity (a) and average voltage (b) of Na+ in the six boron compound structures;
[0037] Figure 5 The unit cell volume and lattice parameters a, b, c of four boron compounds vary with the normalized Na content, where (a) is MnB, (b) is FeB, (c) is CoB, and (d) is NiB;
[0038] Figure 6 (MnFeCoNiZnAl) 1 / 6 B / CNT, (MnFeCoNiZnAl) 1 / 6 X-ray diffraction patterns of B and FeB samples;
[0039] Figure 7 (MnFeCoNiZnAl) 1 / 6 B Transmission electron microscopy images of samples at different magnifications;
[0040] Figure 8 Scanning area for SEM-EDX mapping (a) and (MnFeCoNiZnAl) 1 / 6 Mapping images of Zn, Co, Mn, Fe, Al, Ni, B, and C recorded in B / CNT (bi);
[0041] Fig. 9 (MnFeCoNiZnAl) 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 Infrared absorption spectrum of B;
[0042] Fig.10 (MnFeCoNiZnAl) 1 / 6 B / CNT, (MnFeCoNiZnAl) 1 / 6 N2 adsorption and desorption curves of B and FeB;
[0043] Fig.11 (MnFeCoNiZnAl) 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 Electrochemical impedance spectroscopy results and equivalent circuit diagram of B (inset);
[0044] Fig.12 (MnFeCoNiZnAl) 1 / 6 CV cycle results at different scan rates when B / CNT is used as the positive electrode of sodium ion battery;
[0045] Fig.13 At 1 mV s -1 Pseudocapacitance contribution rate results of CV cycle at scan rate;
[0046] Fig.14 for Fig.11 The redox peak in the middle corresponds to the slope b value;
[0047] Fig.15 The figure is the result of rate cycle test under different current density;
[0048] Fig.16 1A g -1 1000 cycles performance test results under current density;
[0049] Fig.17 This is the trend diagram of pseudocapacitance contribution rate changing with scanning speed. DETAILED DESCRIPTION
[0050] To facilitate understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings, but the present invention can be implemented in different forms and is not limited to the embodiments described in the text. On the contrary, these embodiments are provided to make the content disclosed in the present invention more thorough and comprehensive.
[0051] Example 1: A high entropy boride supported by carbon nanotubes (MnFeCoNiZnAl-B / CNT) was prepared by the following steps:
[0052] S1. Raw material preparation:
[0053] Metal salts: Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O, mixed in a molar ratio of 1:1:1:1:1:1. These metal salts were selected based on their ability to provide the required metal ions when forming high-entropy borides and ensure that the final product has high-entropy properties. The specific ratio of the metal salts was determined based on experimental design and theoretical calculations to achieve the best electrochemical performance.
[0054] Boric acid (H3BO3): added at a ratio of 1:2 to the total molar ratio of the metal salt to ensure that the ratio of boron element to metal element is suitable for forming the desired boride.
[0055] Carbon nanotubes (CNTs): pre-cleaned and dispersed in deionized water. CNTs are used to provide a three-dimensional network support structure, increase the specific surface area and conductivity of the material, and avoid particle aggregation.
[0056] S2. Synthesis process:
[0057] (1) Dissolve the metal salt and boric acid in deionized water under ice bath conditions and stir evenly to obtain a mixed solution containing uniformly dispersed metal ions and borate ions, thereby providing uniform reactants for subsequent reactions.
[0058] (2) Add CNT dispersion to the mixed solution of step (1) in an amount of 1:10 by weight of the total weight of the metal salt. Continue stirring for 30 minutes. The purpose of this step is to evenly disperse the CNTs in the solution and ensure that the CNTs are evenly mixed with the mixed solution, thus laying a foundation for forming a CNT support structure.
[0059] (3) The mixed solution with CNT added was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 180°C for 24 hours. The purpose of the hydrothermal reaction at high temperature is to promote the chemical reaction between metal ions and borate ions to form a high-entropy boride, and the high-entropy boride (MnFeCoNiZnAl-B) is combined with the carbon nanotubes by a chemical liquid phase method.
[0060] The reasons why high entropy borides have an amorphous structure are: ① Rapid reduction reaction: In step (1), H3BO3 reacts rapidly with the metal salt solution as a reducing agent. This rapid reaction may result in the intermediate not having enough time to form a crystal structure, thereby generating an amorphous material. ② Complexity of chemical composition: The complex composition of mixed metals and boron may lead to interactions and solubility problems between different metals, further affecting the formation of the crystal structure and easily leading to an amorphous product. ③ Low temperature conditions: In step (1), the reduction reaction is carried out under ice bath conditions. The low temperature environment may inhibit the growth of crystals, causing the intermediate product to exist in an amorphous state. These factors combined result in the final boride being amorphous.
[0061] The amorphous high entropy boride contains a variety of multivalent metals, creating abundant redox active sites for energy storage.
[0062] (4) After the reaction is completed, the mixture is cooled naturally to room temperature, and the product is centrifuged and washed with deionized water and ethanol for three cycles to remove possible impurities and unreacted products. The washing process is to add deionized water or alcohol, shake, and ultrasonicate to evenly disperse the product in the solution, and then centrifuge the product to complete one wash.
[0063] (5) Finally, the product was dried at 80 °C for 11 hours, and the resulting black powder was a high entropy boride / carbon nanotube composite material, namely (MnFeCoNiZnAl) 1 / 6 B / CNT, has excellent electrochemical performance.
[0064] Embodiment 2: This embodiment differs from Embodiment 1 in that:
[0065] When preparing the raw materials, Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O were mixed in a molar ratio of 0.9:1:1:1:0.9:1.1;
[0066] Boric acid (H3BO3): added at a molar ratio of 1:1.9 to the total metal salt;
[0067] In step (2) of the synthesis process, the CNT dispersion was added to the mixed solution of step (1) and stirring was continued for 40 minutes;
[0068] In step (5), the product is dried at 80° C. for 12 hours.
[0069] The rest is the same as the first embodiment.
[0070] Embodiment 3: This embodiment differs from Embodiment 1 in that:
[0071] When preparing the raw materials, Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O were mixed in a molar ratio of 1.1:1:0.9:0.9:1:1.1;
[0072] Boric acid (H3BO3): added at a molar ratio of 1:2.1 to the total metal salt;
[0073] In step (2) of the synthesis process, the CNT dispersion was added to the mixed solution of step (1) and stirring was continued for 35 minutes;
[0074] In step (5), the product is dried at 80° C. for 12 hours.
[0075] The rest is the same as the first embodiment.
[0076] Example 4: (MnFeCoNiZnAl) prepared in Example 1 1 / 6 B / CNT is used as the positive electrode, metallic sodium is used as the negative electrode, and the electrolyte is an aqueous electrolyte solution to produce an aqueous sodium ion battery.
[0077] Example 5: (MnFeCoNiZnAl) prepared in Example 1 1 / 6 B / CNT is used as the positive electrode, sodium alloy is used as the negative electrode, and the electrolyte is an aqueous electrolyte solution to produce an aqueous sodium ion battery.
[0078] Comparative Example 1: Without using carbon nanotubes (CNT), the other parts are the same as in Example 1, and (MnFeCoNiZnAl) is obtained. 1 / 6 B.
[0079] Comparative Example 2: The metal salt does not use Zn(NO3)2·6H2O and Al(NO3)3·9H2O, and carbon nanotubes (CNT) are not used. The other parts are the same as those in Example 1, and (MnFeCoNi) is obtained. 1 / 4 B, its structural model is shown in the figure Figure 2 (a) shown.
[0080] Comparative Example 3: Directly obtain MnB, FeB, CoB, and NiB materials, and their structural model diagrams are as follows: Figure 2 As shown in (b), (c), (d) and (e).
[0081] The process of theoretical modeling and computational design of the material of the present invention mainly includes the following steps:
[0082] 1. Density functional theory (DFT) calculation: DFT calculation was used to optimize the multi-component boride [(MnFeCoNiZnAl) 1 / 6 B] structure and performance, and determine the optimal structural parameters. Figure 1 As shown, by optimizing the structural model after atomic replacement, a stable unit cell structure was found. At the same time, the order of adsorption sites and the number of adsorptions of sodium atoms were calculated in detail, and a stable structure with two layers of adsorbed sodium ions was obtained.
[0083] 2. Structural prediction: The amorphous structural characteristics of the material and its charge and discharge performance at different voltages were predicted through computational simulation.
[0084] By analysis (MnFeCoNiZnAl) 1 / 6 B in different Na + Formation energy E at adsorption concentration f And simulated discharge voltage to illustrate the present invention (MnFeCoNiZnAl) 1 / 6 The relevant properties of B / CNT are as follows Figure 3 As shown. Figure 3 Calculation shows that (MnFeCoNiZnAl) 1 / 6 The charge and discharge voltage range of B is 0.43-1.62 V, which reflects the (MnFeCoNiZnAl) 1 / 6 B / CNT has obvious wide voltage advantage.
[0085] The ion adsorption mode of the high entropy boride in the present invention is explained by analyzing the changes of the unit cell volume and lattice parameters a, b, and c of the four boron compounds in Comparative Example 3 with the normalized Na content. The results are as follows: Figure 5 As shown, (a) is MnB, (b) is FeB, (c) is CoB, and (d) is NiB.
[0086] Depend on Figure 5 It can be seen that with the adsorption of sodium ions, the volume of all materials gradually increases. Since some borides have a two-dimensional structure, the lattice remains almost unchanged in the a and b directions, and the growth trend in the c direction should be consistent with the overall volume change trend, which is the main driving factor for structural change. This ion adsorption method will most likely ensure that the structural stability of the material is not destroyed during the battery charging and discharging process, which is a necessary condition for long-life batteries. The high entropy boride of the present invention contains Mn, Fe, Co, and Ni, and also has the aforementioned properties.
[0087] 3. Performance evaluation: The maximum theoretical sodium ion adsorption capacity and rated capacity were evaluated.
[0088] Analysis (MnFeCoNiZnAl) 1 / 6 B. (MnFeCoNi) 1 / 4 Na in the structures of six boron compounds: B, FeB, MnB, CoB, and NiB + The maximum theoretical specific capacity and average voltage are shown in the following table. Figure 4 shown.
[0089] Depend on Figure 4 It can be seen that (MnFeCoNiZnAl) 1 / 6 The maximum theoretical specific capacity of B reached a maximum value of 827.69 mAh g -1 , and the average voltage is 0.451 V. Then the (MnFeCoNiZnAl) 1 / 6 B / CNT also has a unique structure and composition, which significantly improves the battery capacity compared with similar materials (MnFeCoNiZnAl) 1 / 6 B / CNT will have a wider range of adaptability in matching the positive and negative electrodes of batteries.
[0090] The material characterization and electrochemical performance of the high entropy boride / carbon nanotube composite material prepared in the example are observed below:
[0091] (1) Analyze the amorphous structure of the material by X-ray diffraction (XRD), such as Figure 6 As shown, for (MnFeCoNiZnAl) 1 / 6 B / CNT, (MnFeCoNiZnAl) 1 / 6The B and FeB samples were subjected to X-ray diffraction (XRD) analysis.
[0092] Depend on Figure 6 It can be seen that (MnFeCoNiZnAl) 1 / 6 B shows obvious amorphous characteristic peaks, while (MnFeCoNiZnAl) with added carbon nanotubes 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 B shows similarity, except for a carbon peak at about 23°, there are no other sharp diffraction peaks. This also shows that CNT as a raw material addition plays a structural support role for amorphous boride, but does not affect the amorphous (MnFeCoNiZnAl) 1 / 6 The synthesis process of structure B.
[0093] (2) Observe the microscopic morphology of the material by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), such as Figure 7 and Figure 8 shown.
[0094] Figure 7 (MnFeCoNiZnAl) 1 / 6 Transmission electron microscopy images of B / CNT samples at different magnifications. Figure 7 It can be seen that at low magnification, (MnFeCoNiZnAl) 1 / 6 B / CNT presents obvious irregular nanoparticles with uniform and small size. No clear diffraction stripes were observed under high magnification, but clearer nanoparticle stacking with a size of about 10nm. Compared with other high entropy compounds, the size has been greatly reduced, indicating that a simple chemical liquid phase method can successfully prepare amorphous (MnFeCoNiZnAl) 1 / 6 B / CNT.
[0095] Figure 8 Among them, (a) is (MnFeCoNiZnAl) 1 / 6 SEM-EDX mapping scanning area of B / CNT sample, (bi) is in (MnFeCoNiZnAl) 1 / 6 Mapping images of Zn, Co, Mn, Fe, Al, Ni, B and C (carbon) recorded in B / CNT. Figure 8 It can be seen that all elements in (MnFeCoNiZnAl) 1 / 6 B / CNT is evenly distributed without obvious biased aggregation. This uniform distribution is not only achieved on the basis of high entropy structure, but also promotes more dispersed active sites in electrochemistry, thereby maximizing the structural entropy.
[0096] (3) Evaluate the electrochemical properties of the material through electrochemical testing.
[0097] Fig. 9 Provides (MnFeCoNiZnAl) 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 Infrared absorption spectrum of B;
[0098] Depend on Fig. 9 It can be seen that (MnFeCoNiZnAl) 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 The UV absorption spectra of B are not much different, which verifies the successful introduction of CNTs.
[0099] Fig.10 Provides (MnFeCoNiZnAl) 1 / 6 B / CNT, (MnFeCoNiZnAl) 1 / 6 N2 adsorption and desorption curves of B and FeB;
[0100] pass Fig.10 N2 adsorption measurements show that CNT-supported amorphous materials are superior to (MnFeCoNiZnAl) 1 / 6 B and FeB, with higher specific surface areas and wider pore size distribution, can provide more active sites for redox reactions in the energy storage process.
[0101] Fig.11 Provides (MnFeCoNiZnAl) 1 / 6 B / CNT and (MnFeCoNiZnAl) 1 / 6 Electrochemical impedance spectroscopy results and equivalent circuit diagram of B (inset);
[0102] pass Fig.11 It can be seen that the electrode shows the smallest semicircle (116.3 Ω) in the high to medium frequency range, which is significantly reduced compared to the other 272.5 Ω resistance, which will greatly improve the charging and discharging effect of the battery, highlighting its advantage in enhancing the surface electrochemical reaction rate.
[0103] Fig.12 Provides (MnFeCoNiZnAl) 1 / 6 CV cycles of B / CNT as the cathode of sodium-ion batteries at different scan rates;
[0104] Fig.12 The cyclic voltammetry curves obtained at different scan rates are shown, where the A and B peaks indicate the material's fast redox reaction ability, that is, fast charge and discharge performance.
[0105] Fig.13 Provides a 1 mV s -1 Pseudocapacitance contribution rate of CV cycle at scan rate;
[0106] Fig.13 The relationship between the total capacitance and the diffusion capacitance is shown at a scan rate of 1 mV / s, where 84.47% of the capacitance comes from the diffusion capacitance, revealing the material's excellent electrochemical activity and ion diffusion capability.
[0107] Fig.14 Provided Fig.11 The redox peak in the middle corresponds to the slope b value;
[0108] Fig.14 By fitting the redox peaks A and B, the slope b values (0.33 and 0.41) obtained reflect the fast electrochemical reaction kinetics of the material.
[0109] Fig.15 Provides rate cycle tests at different current densities;
[0110] Fig.15 Rate performance tests at different current densities showed that the material exhibited good capacity retention and reversibility after undergoing varying charge and discharge currents, demonstrating its stable electrochemical performance.
[0111] Fig.16 Provides 1 A g -1 1000 cycles performance test under current density;
[0112] Fig.16 The coulombic efficiency and specific capacity were stably maintained during the 1000-cycle performance test, demonstrating the excellent long-term cycle stability of the material.
[0113] Fig.17 The variation trend of pseudocapacitance contribution rate with scanning speed is provided;
[0114] Fig.17 The increase in pseudocapacitance contribution with increasing scan rate indicates that the material has better performance under fast charge and discharge conditions, further confirming its potential as a high-performance sodium-ion battery cathode material.
[0115] From the above, it can be seen that the battery prepared by the present invention has the following performance indicators:
[0116] ① Specific capacity: The prepared battery is tested for performance using the Blue Power Battery Test System. -1 At a current density of 1.3 mAh g -1 This is due to the high theoretical sodium ion adsorption capacity of high entropy borides and the high conductivity of CNTs.
[0117] ②Cyclic stability: Fig.16 After the stability test, the results showed that at 1 A g -1 After 1000 cycles at a current density of 1.34 W, the capacity retention rate was 90%, which indicates that the material has good long-term cycle stability.
[0118] ③ Conductivity: Fig.11 The electrochemical impedance spectroscopy was fitted to obtain a conductivity of 100 S cm -1 , this value reflects the high electrical conductivity of the material, which helps to improve the charging and discharging efficiency of the battery.
[0119] ④Wide voltage window: through Figure 3-5 Theoretical calculation results show that the introduction of high entropy borides broadens the voltage window, reduces the average voltage of the material, and makes the positive and negative electrode materials better matched.
[0120] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A carbon nanotube-supported high entropy boride cathode material, characterized in that: The invention comprises carbon nanotubes in a three-dimensional network support structure and high entropy borides attached to the carbon nanotubes, wherein the high entropy borides have an amorphous structure and contain a plurality of multivalent metals; the raw materials of the high entropy boride positive electrode material supported by the carbon nanotubes comprise metal salts, boric acid and carbon nanotubes, the total molar ratio of the boric acid to the metal salt is 1:(1.9-2.1), and the total mass ratio of the carbon nanotubes to the metal salt is 1:
10.
2. The carbon nanotube-supported high entropy boride cathode material according to claim 1, characterized in that: The metal elements of the high entropy boride include Mn, Fe, Co, Ni, Zn and Al.
3. The carbon nanotube-supported high entropy boride cathode material according to claim 2, characterized in that: The metal salts include Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O.
4. The carbon nanotube-supported high entropy boride cathode material according to claim 3, characterized in that: The molar ratios of Mn(NO3)2·6H2O, Fe(NO3)3·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Zn(NO3)2·6H2O and Al(NO3)3·9H2O are (0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1).
5. The carbon nanotube-supported high entropy boride cathode material according to claim 4, characterized in that: The chemical formula of the high entropy boride cathode material is (MnFeCoNiZnAl) 1 / 6 B / CNT.
6. A method for preparing the carbon nanotube-supported high entropy boride positive electrode material according to any one of claims 1 to 5, characterized in that: The steps include: S1. Raw material preparation: taking metal salt, boric acid and carbon nanotubes according to the mass ratio, pre-cleaning the carbon nanotubes and dispersing them in deionized water to prepare a CNT dispersion for later use; S2, dissolving the metal salt and boric acid prepared in step S1 in deionized water under ice bath conditions, stirring evenly to obtain a mixed solution; S3, adding the CNT dispersion to the mixed solution of step S2, and continuing to stir until the mixture is uniform; S4, transferring the mixed solution to which CNTs are added in step S3 to a high-pressure reactor, and performing a hydrothermal reaction to form a desired amorphous high-entropy boride; S5. After the reaction is completed, the mixture is naturally cooled to room temperature, and the product is centrifuged and washed several times with deionized water and ethanol to remove possible impurities and unreacted substances; S6. Dry the product to obtain a black powder which is a high entropy boride / carbon nanotube composite material.
7. The method for preparing a high entropy boride positive electrode material according to claim 6, characterized in that: In step S3, the stirring time is 30-40 minutes.
8. The method for preparing a high entropy boride positive electrode material according to claim 6, characterized in that: In step S4, the temperature of the hydrothermal reaction is 180° C. and the reaction time is 24 hours.
9. The method for preparing a high entropy boride positive electrode material according to claim 6, characterized in that: In step S6, the drying temperature is 80° C. and the drying time is 11-12 hours.
10. An aqueous sodium ion battery, characterized in that: The positive electrode adopts the high entropy boride positive electrode material loaded by carbon nanotubes as described in any one of claims 1 to 5, the negative electrode adopts metallic sodium or sodium alloy, and the electrolyte adopts an aqueous electrolyte solution.
